2015
DOI: 10.1039/c5ra12110h
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and characterization of acrylic acid-2-hydroxyethyl methacrylate IPN hydrogels

Abstract: Three different methods have been developed to crosslink the poly(acrylic acid-2-hydroxyethyl methacrylate) to form the hydrogels having tunable swelling, rheological and morphological properties with applicability in dye and heavy metal removal.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
7
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 41 publications
3
7
0
Order By: Relevance
“…Networks with acrylic acid and HEMA introduced at different amounts exhibited swelling ratios of ∼2500%. This is in agreement with previous studies, which have shown that incorporating acrylic acid into a copolymer network can provide higher water sorption in the system. , Incorporation of the acrylic acid ionic monomer significantly increases the water uptake of hydrogels due to charge repulsion caused by its ionized carboxylic side groups on adjoining polymer chains at pH 7.4. , In contrast, HEMA contains a nonpolar methyl side group and as a result is hydrophobic relative to acrylic acid, which accounts for the significantly lower swelling ratios obtained . As will be shown by the SEM micrographs and in agreement with the literature, , we found a close correlation between the swelling ratios of the hydrogels and their internal microstructure.…”
Section: Resultssupporting
confidence: 92%
See 2 more Smart Citations
“…Networks with acrylic acid and HEMA introduced at different amounts exhibited swelling ratios of ∼2500%. This is in agreement with previous studies, which have shown that incorporating acrylic acid into a copolymer network can provide higher water sorption in the system. , Incorporation of the acrylic acid ionic monomer significantly increases the water uptake of hydrogels due to charge repulsion caused by its ionized carboxylic side groups on adjoining polymer chains at pH 7.4. , In contrast, HEMA contains a nonpolar methyl side group and as a result is hydrophobic relative to acrylic acid, which accounts for the significantly lower swelling ratios obtained . As will be shown by the SEM micrographs and in agreement with the literature, , we found a close correlation between the swelling ratios of the hydrogels and their internal microstructure.…”
Section: Resultssupporting
confidence: 92%
“…On the other hand, increasing secondary chemical interactions between the components of the hydrogels, for instance hydrophobic interactions between the aromatic backbone of f-PEDOT and the nonpolar methyl group of HEMA, will result in significant increase in the stiffness of the network, as was observed for PEDOT_AA_3HEMA and PEDOT_HEMA. Similar hydrophobic interactions have been observed for HEMA containing hydrogels assessed for the removal of aromatic dyes, such as methyl violet and fuschine . The study reported that the presence of the HEMA component in the hydrogels resulted in a higher efficiency in removing these aromatic dyes from solutions due to these secondary interactions.…”
Section: Resultssupporting
confidence: 67%
See 1 more Smart Citation
“…23 Moreover, hydrophilic polymers such as polyHEMA are not strong in water. 24 In general, acrylamide monomers are more reactive than methacrylates. 25 We therefore used a novel multi-functional acrylamide monomer as a hydrophilic monomer.…”
Section: Curing Quality Degree Of Conversion and Depth Of Curementioning
confidence: 99%
“…Interpenetrated polymer network (IPN) hydrogels are dened as a combination of two or more polymer networks which are formed by synthesis in juxtaposition. 23,24 Many investigations were performed to synthesis new structures of IPN hydrogels based on synthetic polymers and polysaccharides. 25 The most employed polysaccharides consist in: chitosan, 26,27 alginate, [28][29][30] starch, [31][32][33][34] salecan, 35 cellulose, 36,37 carboxymethylcellulose, 38,39 etc.…”
Section: Introductionmentioning
confidence: 99%